Ocular heterotopic bone formation in a guinea pig: A case report with 7‐month follow‐up using advanced ophthalmic imaging technology. Issue 6 (24th March 2021) - Goto, So; Zhu, Qiurong; Jensen, Kelly; Torres, Josue A.; Wildsoet, Christine F.
Abstract: Advanced ophthalmic imaging techniques can provide important clinical insights into the pathophysiological changes in heterotopic bone formation (HBF). This case report revealed progression of ocular HBF in the guinea pig over a period of 7 months. Abstract : Advanced ophthalmic imaging techniques can provide important clinical insights into the pathophysiological changes in heterotopic bone formation (HBF). This case report revealed progression of ocular HBF in the guinea pig over a period of 7 months.